Síntese dos feromônios de: Lasioderma serricorne (Coleoptera : Anobiidae) e Lobesia botrona (Lepidoptera : Tortricidae) - Santos, Larissa Cavalcante dos (2017)
A current strategy in pest monitoring and/or control is the use of pheromones, which is based on a safe environmental management approach, an alternative considered quite refined and required in the most industrialized countries. The present work is divided in two chapters. In chapter 1 are described synthetic routes to obtain the sex pheromone of the species Lasioderma serricorne (7-hydroxy-4,6-dimethyl-3-nonanone/serricornine), popularly known as tobacco beetle or cigarette beetle. Synthetic routes for the synthesis of (7E,9Z)-dodeca-7,9-dienyl acetate, (7E, 9Z)-dodeca-7,9-dien-1-ol and (7E,9E)-dodeca-7,9-dienyl acetate are described in chapter 2, pheromone molecules of the European moth, Lobesia botrana, one of the most important pest of the vine. Serricornine was synthesized following the proposed route. The route followed to obtain the pheromonal components of L. botrana was partially completed, lacking the final steps to obtain them. The routes were efficient for the synthesis of the target molecules, presenting satisfactory and practically viable yields.